Interictal magnetoencephalography used in magnetic resonance imaging-negative patients with epilepsy - Wu, Xueqing; Rampp, Stefan; Buchfelder, Michael; Kuwert, Torsten; Blümcke, Ingmar; Zhou, D.; Stefan, Herrmann; Dörfler, Arnd (Acta Neurologica Scandinavica, 2013)
Purpose: This study aims to investigate the contributions of magnetoencephalography (MEG) in magnetic resonance imaging (MRI)-negative patients. Methods: A total of 18 MRI-negative patients diagnosed with refractory epilepsy, subjected to MEG investigation, and subsequently underwent surgery were selected for retrospective analysis. A 1.5-tesla Magnetom Sonata with an eight-channel head array coil was used. MEG data were obtained using a 74/248-channel system. Results: A total of 16 patients (16/18) had positive MEG results, comprising 12 patients with monofocal localizations, five with multifocal localizations, and one with unremarkable results in MEG. In addition, 12 patients had indicative single photon-emission computed tomography (SPECT), five had indicative fluorodeoxyglucose positron emission tomography (FDG-PET), and all the patients had intracranial electroencephalography (EEG) (14 with subdural electrodes and four with electrocorticography). The intracranial EEG recordings of nine patients were guided by MEG informative results. Among these 18 patients, 10 exhibited good postoperative outcomes (Engel I and II), four of which were completely seizure-free. All these ten patients had clear monofocal localization in MEG, including nine with accordant indicative metabolic changes in either SPECT or FDG-PET, or both. None of the five patients with multifocal localizations achieved good postoperative outcomes. Conclusion: For cases with negative MRI findings, epilepsy surgery may be an alternative option for pharmaco-resistant patients if epileptogenic focus localizations by MEG are present in multimodal evaluation. © 2012 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Magnetic resonance imaging; Magnetoencephalography; Non-lesional epilepsy; Outcome